PEMANFAATAN PATI KULIT UBI KAYU DAN SELULOSA KULIT KACANG TANAH PADA PEMBUATAN PLASTIK BIODEGRADABLE - ARIF BUDIANTO; DEWI FORTUNA AYU; VONNY SETIARIES JOHAN (Universitas Riau, 2019)
Biodegradable plastic is an environmental friendly plastic made from starch and cellulose. Starch andcellulose were extracted from cassava peel and peanut shell. The purpose of this research was to get the bestformulation of cassava peel starch and peanut shell as cellulose on physical and mechanical properties ofbiodegradable plastics. This research was conducted experimentally by using complete randomized design(CRD) which consist of five treatment and three replications, thus analyzed by ANOVA and followed byduncan’s new multiple range test (DNMRT) at level 5%. The treatments in this research were PS1 (starchcassava peel 10 g), PS2 (9.5 g starch cassava peel : 0.5 g cellulose peanut shells), PS3 (9 g starch cassavapeel : 1 g cellulose peanut shells), PS4 (8.5 g starch cassava peel : 1.5 g cellulose peanut shells), and PS5 (8g starch cassava peel : 2 g cellulose peanut shells) in biodegradable plastic formulation. The results ofANOVA showed that the starch of cassava peel and cellulose peanut gave a significant effect on waterresistance, water vapor transmission, biodegradation time, tensile strength, and elongation. The selectedtreatment was PS4 which had water resistance of 15.90%, water vapor transmission of 6.77 g/m2/h,biodegradation time for 8 days, tensile strength of 2.72 MPa, and elongation of 8.75%.